Privacy in the 21st Century - Rengel, Alexandra (Studies in intercultural human rights., 2013)
In Privacy in the 21st Century Alexandra Rengel offers an assessment of the International right to privacy within both a historical and modern context with a focus on the legal aspects of the right, its evolution and its future protection.